Kompetensi Sosial Guru Pendidikan Agama Katolik dan Budi Pekerti dalam Program Sekolah Ramah Anak pada Sekolah Menengah Pertama Katolik - Clara Wetuq Dea; G. Simon Devung; Nikolaus Anggal (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2023)
This research aims to determine the social competence applied by Catholic Religious Teachers in three aspects, namely: 1) acting objectively and non-discriminatorily towards students, 2) communicating effectively, empathetically, politely with students, and 3) adapting to students who have social diversity and culture. The research was conducted at Barong Tongkok Catholic Junior High School, using a descriptive qualitative approach. Research data collection techniques use interview, observation, and documentation methods. There were informants in this study: the principal, teachers of Catholic religious education, students, and ordinary teachers. The results of this research show that the social competence of teachers applied by Catholic Religious Teachers is good, which is demonstrated by treating students objectively without discriminating, behaving, and acting fairly, giving equal attention and opportunities to all students. Teachers also act in accordance with their duties and functions, namely listening to the person they are talking to, speaking using standard language, being able to adapt and feel at home carrying out their duties as a teacher. In this way, the Child Friendly School Program becomes a forum for Catholic Religious Teachers to develop their social competencies well through collaboration with all school parties.